2005
DOI: 10.1093/jurban/jti110
|View full text |Cite
|
Sign up to set email alerts
|

Risk Behaviors and HIV/AIDS Prevention Education Among IDUs in Drug Treatment in Shanghai

Abstract: We estimated seroincidence of HIV, hepatitis B virus (HBV) and hepatitis C virus (HCV), and the prevalence of risk behaviors among injection drug users (IDUs) who accepted inpatient detoxification by 14-day methadone tapering treatment in the Shanghai Drug Abuse Treatment Center. We also evaluated the effect of an HIV/AIDS prevention education intervention on those IDUs. Data including demographic characteristics, HIV, HBV and HCV seroincidence, sexual and injection-related risk behaviors were collected from 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 13 publications
2
12
0
Order By: Relevance
“…Among 25 studies, eight studies targeted FSWs (Ma et al 2002; Lau et al 2007; Li et al 2006; Liao et al 2006; Rou et al 2007; Wu et al 2007b; Yang et al 2005; Zhongdan et al 2008), seven studies targeted IDUs (Chen et al 2007; Des Jarlais et al 2007; Lau et al 2008; Lin et al 2004; Pang et al 2007; Wu et al 2007a; Zhao et al 2005), one study targeted HIV sero-discordant couples (Yang et al 2001), one for health workers (Wu et al 2002a), and one for MSM (Gao and Wang 2007). The remaining eight studies targeted the general population, including four for youths or students (Cheng et al 2008; Li et al 2008; Tian et al 2007; Wang et al 2005), two for general villagers in the areas with high HIV prevalence (Tian et al 2007; Wu et al 2002a), one for pregnant women (Khoshnood et al 2006), and one for female factory workers (Qian et al 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Among 25 studies, eight studies targeted FSWs (Ma et al 2002; Lau et al 2007; Li et al 2006; Liao et al 2006; Rou et al 2007; Wu et al 2007b; Yang et al 2005; Zhongdan et al 2008), seven studies targeted IDUs (Chen et al 2007; Des Jarlais et al 2007; Lau et al 2008; Lin et al 2004; Pang et al 2007; Wu et al 2007a; Zhao et al 2005), one study targeted HIV sero-discordant couples (Yang et al 2001), one for health workers (Wu et al 2002a), and one for MSM (Gao and Wang 2007). The remaining eight studies targeted the general population, including four for youths or students (Cheng et al 2008; Li et al 2008; Tian et al 2007; Wang et al 2005), two for general villagers in the areas with high HIV prevalence (Tian et al 2007; Wu et al 2002a), one for pregnant women (Khoshnood et al 2006), and one for female factory workers (Qian et al 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Previous study showed that IDUs with a history of overdose were more often involved in high-risk situations such as sex work [12], which might increase the risky behavior of unprotected sex. Since there is neither a cure nor a vaccine against HIV/AIDS, educating IDUs’ about HIV transmission and reducing their high-risk behaviors provide an important protection against the infection concerned [18,19]. …”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first study in mainland China to evaluate an MMT program, and the results suggest positive effects on drug-using and risky sexual behaviors. Methadone has been widely used for short-term detoxification purposes in China since 1993; however, the relapse rate was high after cessation of methadone (Liu, Zhao, Lu, Wang, & Zhang, 2004;Tang, Zhao, Zhao, & Cubells, 2006;Zhao et al, 2005). Therefore, the Chinese government initiated methadone maintenance in 2004 with the hope of enhancing treatment effectiveness and reducing HIV risks among IDUs -the most afflicted subgroup in this country.…”
Section: Discussionmentioning
confidence: 99%